Biochar regulates the functions of keystone taxa to reduce p-coumaric acid accumulation in soil - Zhu, Xuanquan; Jia, Meng; Zi, Dingchun; Zhou, Peng; Du, Yu; Wang, Na; Dai, Huijuan; Wang, Ge; Bai, Yuxiang (Frontiers in Microbiology, 2024)
Applying biochar (BC) to reduce toxic substance accumulation in soil, either through direct adsorption or modulation of the microbial community, has received considerable attention. However, a knowledge gap exists regarding how BC regulates microbial community structure and functions to mitigate toxic substance accumulation. We previously identified p-coumaric acid (p-CA) as a representative autotoxin in tobacco rhizosphere soil. On this basis, this study simulated a soil environment with p-CA accumulation to investigate the impacts of BC on p-CA, soil physicochemical properties, and microbial community structure and function. The results showed that p-CA could be directly adsorbed onto BC, which followed the pseudo-second-order kinetic model (R 2 = 0.996). A pot experiment revealed that BC significantly reduced soil p-CA, altered soil microbial composition, and enhanced bacterial community diversity. A weighted correlation network analysis showed a close association between taxon 1 in the microbial network and p-CA, suggesting a pivotal role for this taxon in reducing p-CA, with Devosia and Nocardioides identified as potential key contributors to this process. The prediction of possible keystone taxa functions showed that BC increased the relative abundances of aromatic compound degraders. Mantel tests indicated that soil organic matter exerted the greatest influence on keystone taxa functions and hub genera. These findings suggest that BC may either directly chemisorb p-CA or indirectly facilitate p-CA degradation by regulating the functioning of keystone taxa. The results of this study provide a novel perspective for further investigation of the mechanisms through which BC reduces the accumulation of toxic substances in soil.